Green Perceived Quality Impact on Purchase Intention: Roles of Awareness and Value - Alfina Priyanidewi, Pipin; Hadi, Effed Darta (Universitas Negeri Semarang, 2025)
This study examines the influence of green perceived quality on green purchase intention in the skincare industry. As consumers increasingly demand environmentally responsible products, understanding the drivers of green consumer behavior becomes essential. This research investigates the relationship between green perceived quality and green purchase intention through green perceived value, with environmental awareness acting as a moderating variable. A quantitative method was employed through an online survey distributed to 270 purposively selected consumers of Avoskin, a skincare brand in Indonesia. Data were analyzed using Structural Equation Modeling with Partial Least Squares. The results indicate that green perceived quality significantly effects green purchase intention, both directly and through green perceived value. Moreover, environmental Awareness strengthens the relationship between Green Perceived Quality and Green Purchase Intention. This study contributes to the understanding of green consumer behavior by highlighting the dual role of Green Perceived Value and Environmental Awareness. Practical implications include guidance for skincare marketers to enhance consumer perception and awareness, thereby increasing purchase intention toward sustainable cosmetic products.